On the r-dynamic coloring of subdivision-edge coronas of a path - Nandini, G.; Venkatachalam, M.; M. Falcón, Raúl (AIMS mathematics, 2020)
This paper deals with the r-dynamic chromatic number of the subdivision-edge corona of a path and exactly one of the following nine types of graphs: a path, a cycle, a wheel, a complete graph, a complete bipartite graph, a star, a double star, a fan graph and a friendship graph.